A Spational/Functional Analysis of Late Fourth Millennium Occupation at the TUV mound, Tall-e Malyan, Iran - Nicholas, Ilene Mildred (1980)
2 vols.; Ph.D. Dissertation; Supervisor: R.H.Dyson, Jr. Order No. 8018593, cf. DissAbstr 41,3 (1980) 1116- A.